What of the following statements have the same result?
f(1) when f(x) = 5x + 1
f−1(3) when f(x) = 2x+3
3y − 7 = y + 5

Hey! We 've verified this expert answer for you, click below to unlock the details :)

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

@jim_thompson5910

f(x) = 5x + 1
f(1) = 5(1) + 1 ... replace every x with 1
f(1) = ???

5

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

Looking for something else?

Not the answer you are looking for? Search for more explanations.